The relative effects of family factors and opportunity factors on juvenile delinquency - Gray, Phyllis A. (1987)
This dissertation focuses on the relative impact of family factors (parental supervision and control, parental rejection, family structure) and perceived blocked opportunities (educational and occupational) on juvenile delinquency. Strain theory claims that delinquency results when youths are unable to achieve monetary success or middle-class status through legitimate means. In contast, social control theory states that delinquency may result when youths' attachments to significant others (i.e., parents) are weakened or broken;The goal of the present research is to determine the relationship between variables derived from the aforementioned theories and the seriousness of delinquency. The predictive powers of the theoretical models will be compared by race and socio-economic status. The total sample consists of 8,375 randomly selected youths. The selected sample used in this research includes only black (N = 293) and white (N = 1,443) males. This racial breakdown is comparable to the national population